Temporal bone imaging findings in Waardenburg's syndrome - (:unkn) unknown (ELSEVIER IRELAND LTD, 2001)
Objective: (a) To report computed tomography findings of eight new cases with Waardenburg's syndrome (WS) type I and review reported temporal bone radiographic and histopathological findings in WS with hearing loss; (b) To determine the frequency of inner ear pathologies that may contraindicate cochlear implantation. Methods: A review of 1166 pediatric patients with sensorineural hearing loss revealed 12 cases (1%) with WS, whose family screenings disclosed additional 12 subjects with the same disorder. Among these 24 cases, eight had WS type I and were subjected to computed tomography scanning of temporal bone. Imaging findings of 28 cases reported previously in English literature were evaluated together with our eight patients. Results: Malformation of the inner ear was found in none of the nine WS type I cases evaluated here, while the frequency of internal acoustic canal malformation was 11%. Regardless of the subtypes of the syndrome, 6 of 36 cases (17%) had radiological abnormality of the inner ear. Malformation and/or absence of the semicircular canals were the most common congenital abnormality of the inner ear. Hypoplasia of the cochlea was present in 3 of 36 cases (8%). Conclusions: Abnormality of bony labyrinth in WS with congenital deafness is not a frequent finding, particularly in WS type I. Therefore, the otologist and audiologist must keep in mind that most of these cases are suitable for cochlear implantation regarding inner ear anatomy. (C) 2001 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Waardenburg's syndrome; temporal bone; imaging; cochlear implantation; SYNDROME TYPE-II; COCHLEAR IMPLANTATION; HEARING-LOSS; MUTATIONS; CHILDREN; GENE; MALFORMATIONS; DISEASE